A three-thousand-year-old soldier: history and the Hebrew Bible in Jewish-Israeli public education. Issue 4 (4th July 2022) - Kisler, Rudy
ABSTRACT: History education has been instrumental in transmitting collective memories across generations while sustaining national traditions. Many nations use history education to instill national memories in their future citizens. In the current Jewish context, history is arguably a dominant cultural discourse. History education is deemed central to preparing future Jewish citizens of Israel. In particular, Zionist scholars and educators use the Bible as their primary text, providing an infrastructure of history and myths for this national ideology. In order to investigate the relationship between political ideology, education, and national memories, this paper explores the ways in which the Hebrew Bible and Jewish history are being taught interchangeably in Jewish-Israeli schools. Drawing on various source materials (such as political videos, school curricula, and textbooks), the paper retraces the origins of this conflation, critically examines its goals, and suggests possible effects it may have on the formation of children's and adolescents' collective memories.